(3GdeONd ddYdhe GdbGfhfjI (B:s (3fXQjI GdbGfhf hfXQjI GdMb (B/s - (3HYdj, eMeO GdUZjQs ((3GdLRGFQ (B: s (3OGQ GdYdhe ddfTQ hGdJhRjY(B, s)
(3jVe ebOeI YGeI GdbGfhf hGdeLJeY, fXQjI GdbGfhf , GdbGfhf hUdJg HGdbhGYO GdGLJeGYjI , eUGOQ GdbGfhf , JaSjQ GdbGfhf hfWGb JWHjb GdbGfhf, fXQjI GdMb, GdMb hJbSjeGJg, CQcGf GdMb, BKGQ GdMb hEfbVGA GdMb(B.s
(3HjHjdhZQGajG(B: (3U U(B225-226s
Keywords: (3GdMbs; (3GdbGfhfs; (3GdbGfhf(B- (3fXQjGJs